Circulating cell-free microRNAs as clinical cancer biomarkers - Armand-Labit Virginie; Pradines Anne (Biomolecular Concepts, 2017)
MicroRNAs (miRNAs) are non-coding small RNAs that are master regulators of genic expression and consequently of many cellular processes. But their expression is often deregulated in human tumors leading to cancer development. Recently miRNAs were discovered in body fluids (serum, plasma and others) and their levels have often been reported to be altered in patients. Circulating miRNAs became one of the most promising biomarkers in oncology for early diagnosis, prognosis and therapeutic response prediction. Here we describe the origins and roles of miRNAs, and summarize the most recent studies focusing on their usefulness as cancer biomarkers in lung, breast, colon, prostate, ovary cancers and melanoma. Lastly, we describe the main methodologies related to miRNA detection, which should be standardized for their use in clinical practice.